Coping strategies during the experience of breast cancer (Research, Society and Development, 2021)
Aiming to know the coping of women diagnosed and treated for breast cancer, through life reports, a qualitative study, of the Oral History type, was carried out in 2016 with five women from the interior of Northeastern Brazil. Data collection took place through semi-structured interviews at the participants' homes, after prior contact with the health institution to which they were linked. The interviews were recorded, transcribed and analyzed, according to Bardin's content analysis technique and the help of the Web Qualitative Data Analysis (WebQDA) software. From the reports, the following categories emerged: Self-Control Attitudes and Social Support in Coping with Breast Cancer, and Religious Coping in Breast Cancer. The women in the study expressed self-control, social support and religious coping in coping with the diagnosis and treatment of breast cancer. For the planning of nursing care and the multidisciplinary team, it is important to know the woman's coping during the diagnosis and treatment of breast cancer.